Adiponectin treatment attenuates inflammatory response during early sepsis in obese mice - Wang X; Buechler NL; Yoza BK; McCall CE; Vachharajani V (Dove Medical Press, 2016)
XianFeng Wang, Nancy L Buechler, Barbara K Yoza, Charles E McCall, Vidula Vachharajani Department of Anesthesiology, Medicine and Surgery, Wake Forest School of Medicine, Winston-Salem, NC, USA Background: Morbid obesity increases the cost of care in critically ill patients. Sepsis is the leading cause of death in noncoronary intensive care units. Circulating cell–endothelial cell interactions in microcirculation are the rate-determining factors in any inflammation; obesity increases these interactions further. Adiponectin deficiency is implicated in increased cardiovascular risk in obese patients. We have shown that adiponectin deficiency increases microvascular dysfunction in early sepsis. In the present study, we investigated the effect of adiponectin replacement on nutritionally obese mice with early sepsis. Methods: We used cecal ligation and puncture model of sepsis in mice with diet-induced obesity (DIO) vs control diet (CTRL), with or without adiponectin treatment. We studied leukocyte/platelet adhesion in the cerebral microcirculation in early sepsis. We also studied the effect of adiponectin on free fatty acid (FFA)-fed and lipopolysaccharide-stimulated bone marrow-derived macrophages (BMDM) for mechanistic studies. Results: Leukocyte and platelet adhesion increased in the cerebral microcirculation of DIO and CTRL mice with early sepsis vs. sham; moreover cell adhesion in DIO-sepsis group was significantly higher than in the CTRL-sepsis group. Adiponectin replacement decreased leukocyte/platelet adhesion in CTRL and DIO mice. In FFA-fed BMDM, adiponectin treatment decreased tumor necrosis factor-alpha mRNA expression and increased sirtuin-1 (SIRT1) mRNA expression. Furthermore, using BMDM from SIRT1 knockout mice, we showed that the adiponectin treatment decreased inflammatory response in FFA-fed BMDM via SIRT1-dependent and -independent pathways. Conclusion: Adiponectin replacement attenuates microvascular inflammation in DIO-sepsis mice. Mechanistically, adiponectin treatment in FFA-fed mouse macrophages attenuates inflammatory response via SIRT1-dependent and -independent pathways. Keywords: sepsis, obesity, adiponectin, leukocyte adhesion, inflammation, sirtuin-1